HOTS-Based RADEC Learning Model Improves Critical Thinking Skills in Integrated Islamic Elementary School Students - Muhammad Yaumi; Azisah; Misykat Malik Ibrahim; Abrina Maulidnawati Jumrah (Universitas Pendidikan Ganesha, 2026)
The quality of education in Indonesia continues to face various challenges. Existing instructional practices are often considered ineffective in fostering students’ interests and potential, as reflected in low levels of engagement and responsiveness during learning activities. In response to this issue, this study aims to develop a Higher Order Thinking Skills (HOTS)-based RADEC (Read, Answer, Discuss, Explain, and Create) learning model for students in Integrated Islamic Elementary Schools. This study employed a research and development (R&D) approach using the ADDIE model as the instructional design framework. The trial subjects consisted of 61 students involved in limited and expanded trials of the HOTS-based RADEC learning model. The research involved expert validation from two learning model experts, two practitioner teachers, two guidebook experts, two instructional module validation experts, two instrument validity experts, two teacher response questionnaire validation experts, and two student response questionnaire validation experts. Data were collected through observations, interviews, questionnaires, tests, and documentation. The data collection instruments included observation sheets, interview guidelines, and questionnaires. Data analysis techniques comprised qualitative and quantitative descriptive analyses. The findings indicate that the HOTS-based RADEC learning model was deemed valid based on expert validation results. Teacher and student response tests also demonstrated that the model was practical to implement. Furthermore, effectiveness testing revealed that the HOTS-based RADEC learning model significantly improved students’ critical thinking skills. It can be concluded that the HOTS-based RADEC learning model is feasible and effective for implementation in elementary school learning contexts.